2021
DOI: 10.1016/j.jtho.2020.10.127
|View full text |Cite
|
Sign up to set email alerts
|

Lung Screening Benefits and Challenges: A Review of The Data and Outline for Implementation

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide, accounting for almost a fifth of all cancerrelated deaths. Annual computed tomographic lung cancer screening (CTLS) detects lung cancer at earlier stages and reduces lung cancer-related mortality among high-risk individuals. Many medical organizations, including the U.S. Preventive Services Task Force, recommend annual CTLS in high-risk populations. However, fewer than 5% of individuals worldwide at high risk for lung cancer have undergone sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 94 publications
0
48
0
Order By: Relevance
“…Between 2019 and early 2020, seventy-four percent of patients who qualified for lung cancer screening received such screening through our Tobacco Treatment Clinic, significantly higher than the U.S. average of 4% ( Sands et al, 2021 ). The majority of such patients in our study were African American and/or from socioeconomically disadvantaged neighborhoods, both of which are sociodemographic variables known to result in lower lung cancer screenings ( Jemal and Fedewa, 2017 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Between 2019 and early 2020, seventy-four percent of patients who qualified for lung cancer screening received such screening through our Tobacco Treatment Clinic, significantly higher than the U.S. average of 4% ( Sands et al, 2021 ). The majority of such patients in our study were African American and/or from socioeconomically disadvantaged neighborhoods, both of which are sociodemographic variables known to result in lower lung cancer screenings ( Jemal and Fedewa, 2017 ).…”
Section: Discussionmentioning
confidence: 94%
“…However, despite such evidence, lung cancer screening has been underutilized in the US ( Pham et al, 2020 , Jemal and Fedewa, 2017 , Soneji et al, 2017 ). For instance, only 4% of eligible patients undergo lung cancer screening ( Sands et al, 2021 ), and 18% of current US adult smokers reported a discussion with their healthcare providers regarding lung cancer screening in the prior year ( Soneji et al, 2020 ). Further, there are health disparities in regards to lung cancer screenings in the US, specifically amongst African Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical segmentectomy has been considered for many years a rescue resection procedure only for high risk patients deemed inoperable for lobar resection due to decreased pulmonary function or comorbidity (1). However, as minimally invasive thoracic surgery developed, the idea of lung-sparing resection became more attractive for thoracic surgeons, especially due to advances in early diagnosis and lung cancer screening programs already available in some countries (2)(3)(4). Many studies show evidence that anatomical segmentectomies are oncologically correct for some subtypes of early stage non-small cell lung cancer (NSCLC) (5)(6)(7)(8), but their indications are also extended to benign or metastasic central lesions, or even multifocal or recurrent primary cancers (9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nearly 75% of patients diagnosed are already in the terminal stages of the disease. Although it is possible to assess risk and optimize therapy for every patient by clinical and pathological indicators, such as positron emission tomography CT (PET-CT) or pathology results, these indicators cannot be quanti ed to differentiate a patient with low risk from a patient high risk and are not su cient in clearly assessing individual circumstances [5,6]. Thus, a dependable novel signature with early diagnostic e cacy and prognostic predictive power would greatly improve patient care and treatment development.…”
Section: Introductionmentioning
confidence: 99%